Hematopathology : morphology, immunophenotype, cytogenetics, and molecular approaches - Naeim, Faramarz; Rao, P. Nagesh; Grody, Wayne W.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/Academic Press, 2008)
This comprehensive, full color hematopathology reference book emphasizes immunophenotpic features, cytogenetic studies, and diagnostic molecular aspects. Hematopathology begins with introductions to morphologic evaluation of the hematopoietic tissues and principles of immunophenotyping, cytogenetics and molecular studies followed by chapters dedicated to different types of hematologic disorders. Each chapter starts with a basic overview of hematopathlogy followed by a comprehensive review of immunophenotypic, cytogenetic and molecular findings. The text is balanced with large numbers of full color images, graphs, charts, and tables to assist the reader in understanding these highly technical issues. Emphasizes the immunophenotopic features, cytogenetic studies, and diagnostic molecular aspects of hematology. Features a large number of images, charts and tables for the identification of hematologic disorders not only based on histopathologic features, but also with the use of advanced accessory techniques.
Morphologic Evaluation of Hematopoietic Tisues -- Principles of Immunophenotyping -- Principles of Karyotyping -- Principles of Molecular Studies -- Bone Marrow Hypoplasia -- Chronic Myeloproliferative Disorders -- Myelodysplastic Syndrome -- Myeloproliferative/Myelodysplastic Disorders -- Acute Myeloid Leukemias -- Acute Lymphoid Leukemias -- Acute Leukemias of Ambiguous Lineage -- Chronic Lymnphoid Leukemias and Related Disorders -- Malignant Lymphomas -- Monoclonal Gammopathies -- Disorders of Histiocytes and Denditic Cells -- Mastocytosis -- Constitutional and Non-Neoplastic Granulocytic Reactive Lymphoid Disorders -- Disorders of Red Blood Cells -- Disorders of Megakaryocytes and Platelets -- Bone Marrow Transplantation.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Hematology; Blood -- Diseases -- Diagnosis; Blood -- Diseases -- Molecular aspects; Blood -- Diseases -- Genetic aspects; MEDICAL -- Hematology; Hematologic Diseases -- pathology; Cytogenetic Analysis -- methods; Cytogenetics -- methods; Immunophenotyping; Lymphatic Diseases -- pathology; Blutkrankheit; Blood -- Diseases -- Diagnosis; Blood -- Diseases -- Molecular aspects; Hematology; Electronic books